POTENTIALITY AND PERSPECTIVES OF DRAFTING A STANDARD FOR LITHUANIAN BOOK MONUMENTS - BLIŪDŽIUVIENĖ, NIJOLĖ (Knygotyra, 2011)
Each individual library or other institution possessing bibliographical or typographical rarities, old books, outstanding books within the Lituanica collection, iconographic or cartographic documents or other valuable printed materials in their holdings make their own decisions on selection of these materials for conservation and restoration, as well as take the responsibility of preparing methodical recommendations for preservation, cataloguing and use of old publications and archival documents. Lithuania has a long-standing concept of the old or rare (antiquarian) book, and identification criteria as well as preservation requirements for such a book have been established. However, there is no generally accepted method of the protection and registration of printed heritage objects. Therefore, it could be assumed that adoption of a national standard for Lithuanian book monuments would enable to generalize the existing practice and to institute the concept of a book monument which is not covered by legal acts and official terminological sources. It must be underlined that the concept of the book monument is limited to objects with the status of state protection and registration. The standard for Lithuanian book monuments would include general provisions on objects of printed heritage at every level to be designated as book monuments, identification and selection criteria, categories of book monuments, also requirements for their state registration, preservation and use. The standard would provide the background for drafting a list of Lithuanian book monuments, which could constitute part of the State Register of Cultural Objects. Drafting the standard for Lithuanian book monuments should be guided by legal acts regulating the activities of libraries, museums and archives as well as by the Law on Protection of Moveable Cultural Objects; advantages of a close cooperation with book researchers, restoration professionals and government officials should be also taken into consideration. The Technical Committee LST/TC 47 “Information and Documentation” and LST/TC 81 “Conservation of Cultural Property“ of the Lithuanian Standards Board could serve as a foundation for general requirements and rules concerning Lithuanian book monuments to be adopted as a national standard. This, in its turn, would facilitate assignment of the state registration and protection status to the most valuable printed and manuscript heritage objects.